Acupuncture as a Rehabilitative Therapy in Patient with Multiple Sclerosis: A case Study - satyal, jaya; KC, Pradeep; Shrestha, Rabindra; Dhakal, Pratima (Annapurna Journal of Health Sciences, 2023)
Acupuncture is a branch of TCM (Traditional Chinese Medicine) and has been practiced in China for more than 3000 years. It coordinates conventional Chinese needling strategies with Western clinical information on the cerebral cortex and has been demonstrated to be an extremely compelling method for treating Multiple sclerosis (MS) and other focal sensory system issues. A 42-year-old female patient who was diagnosed with MS was treated with Acupuncture therapy. This case shows that Acupuncture therapy can be complimentary treatment in Multiple Sclerosis. Acupuncture therapy that holds the possibility to extend treatment alternatives for MS in both ordinary and integrative treatments.